Energy efficient clustering and topology management scheme for wireless sensor networks. (16th February 2022) - Kelagadi, Hemantaraj M.; Priyatamkumar, G.
The performance of wireless sensor networks (WSNs) is influenced by the node energy conditions. Though clustering technique is significantly found to enhance the scalability and energy efficiency of the overall system, conventional clustering algorithms fail to handle critical circumstances. Data collection from every sensor node is important and at the same time duplication of similar data from several nodes has to be bypassed to avoid excess energy dissipation of the cluster heads required to handle indistinguishable data. An algorithm to control the topology by inclusion of clustering scheme and dynamic TDMA scheduling for data aggregation and classification is proposed in this paper. An avenue planning strategy to control the node faults is introduced to provide alternate paths in case of node failures. Fault tolerance and topology control therefore contend to balance the node energies efficiently. Effectiveness of the proposed scheme is analysed through simulation and the efficacy is verified.